The impact of land use and climate change in the centre region of France on the physico-chemical status of aquatic systems. (2016) - Nedjai, Rachid; Nghiem, Van-Tuan; Do, Thi-Phuong-Thao; Nasredine, Messaoud Nacer
The impact of land use and climate changes on aquatic systems has been the topic of numerous scientific studies because many symptoms have been observed [flows disturbance, content organic carbon and nutrients (P, N) increase, rising of water temperature, generally accompanied by oxygen depletion, acidification and eutrophication]. The goal of this work is to show the direct impact of the land use change observed and climate change on the Loire watershed of France (117, 500 km 2 ), caused by a considerable reduction in farming activity over the past 30 years. The investigation of three dates of Landsat images (1985, 2000 and 2013) allows the detection of the closure landscape and the substitution of grassland by trees, especially in the high areas. Then, the WAMRF (hydrogeochemical model) is applied to calculate the water flows under these new land use and climate conditions. This first step is followed by a predictive phase prior to measuring the evolution of flows over the next 20 years. The results show a clear decrease of the flows during the simulation period (1985 to 2013) which is around 20% to the 2030. In fact, these observations can be related to the enclosure landscape caused by the rural exodus and forest development registered in France since 1970 and the warming by climate change.